u-14=-46

Simple and best practice solution for u-14=-46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for u-14=-46 equation:


Simplifying
u + -14 = -46

Reorder the terms:
-14 + u = -46

Solving
-14 + u = -46

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + u = -46 + 14

Combine like terms: -14 + 14 = 0
0 + u = -46 + 14
u = -46 + 14

Combine like terms: -46 + 14 = -32
u = -32

Simplifying
u = -32

See similar equations:

| 3s-2t/6*12/9s-3t | | h(x)=x(x+2)-x(2x-1) | | 50/x=.47 | | y+(-10)=-8 | | 2x-8/7x=1 | | 18-4k=-10+10k | | z=8-i | | 22+3x=-2-8x | | 2x-7/2=3 | | 5a-20+a*-3=50 | | 25=.60xX | | [3+(4-1)]=x | | 6x+2y=23 | | 3n^2+6-4n^3-8n= | | (4x+4)(3x-8)=0 | | w^2+3w-64=0 | | -5g=-21.1 | | y=ax^3-1 | | 30=si+2*t | | 0=2x^2-72 | | 30=si+2-8*t | | 3x+8y=-56 | | 1-2cosx=o | | 8.00=x-2.75 | | y=3x^2+20x-7 | | -8=35-5q | | -8=35-59 | | f(n)=3n^2-2 | | X^2-15x+24=-3x+4 | | -6x+85=61 | | 1.15a+8-0.42=-7 | | X(10-x)=24 |

Equations solver categories